Polymer action on the alkali-silica reaction - Ribeiro, M. S. (2014)
At the National Laboratory of Civil Engineering (LNEC), Portugal, and with financial support from Fundação para a Ciência e a Tecnologia (FCT) given to the research project PTDC/ECM/101810/2008 – Polymer-modified Cement Mortars for the Repair of Concrete Structures, an ongoing study aims to assess the influence of polymers on the degradation mechanism of cement-based materials due to ASR. For polymer dosages in excess of 10% of the mass of cement a continuous network of polymer film starts to form amongst cement hydrates, effectively transforming the cement matrix into a polymer-cement co-matrix (Figure 1). The effect of this polymer network on the expansion and microcracking resulting from ASR was assessed for a variety of polymer-modified cement-based mortars (PCMs) using acrylic-styrene, styrene-butadiene and epoxy polymers and performance was compared to that of an unmodified cement mortar (CM).